Creative marketing for new product and new business development - Ishikawa, Akira, 1934-; Tsujimoto, Atsushi (World Scientific Pub. Co., 2008)
New products and new business development require innovative, creative marketing solutions in order to successfully differentiate them from competing products in the marketplace. This important book explores and elucidates the essence of creativity, with an emphasis on how to proceed with R & D activities strategically and how to connect them with successful products, services and commercialization. Using interesting, real case studies such as "Healthy TeaTM" developed by Japan Coca-Cola, Inc., the recommendation engine "Teach Me Electronic Appliances", and the development of various robots, the book uncovers the secret of successful marketing and shows how to develop and deploy new products and services on a sustainable basis. It will therefore appeal to both business practitioners as well as researchers and students interested in innovation and marketing issues.